SIGNIFICANT VALUES OF TOURISM LEARNING FOR LOCALS TO SUPPORT TOURISM DEVELOPMENT THROUGH COUNSELING AND MENTORSHIP - Yusri Abdillah; Supriono Supriono; Sunarti Sunarti; Andriani Kusumawati (Universitas Brawijaya, 2020)
A tourism development in an area is basically unable to be separated from the existence of supporting local residents, since the existence of tourism objects is not only to increase a regional income but also to encourage public awareness of tourism activities. The study was conducted by direct observation of counselling and assistance activities on Tourism Awareness by academics in society, followed by in-depth interviews with speakers and participants of counselling and mentoring activities, as well as tourism stakeholders (tourists, Heads of regional tourism offices, and village officials) after the activity was carried out in Gunungronggo Tourism Village, Tajinan District, Malang Regency, East Java, Indonesia. The results showed that learning related to tourism is very important to them. The local people were active (enthusiastic) during the activity because all this time they did not know the tourism importance. During this time they assume tourism will only bring harm because many foreigners (tourists) enter the area. However, numerous positive things can be accomplished with the arrival of foreigners. Finally, the impact of counselling and mentoring activities encourage the locals to fully support tourism activities and they find business opportunities to bring in revenue in the tourism se